Direct growth of Mn(OH)2/Co(OH)2 nanocomposite on carbon cloth for flexible supercapacitor electrodes. (January 2021) - Anjana, P.M.; Sarath Kumar, S.R.; Rakhi, R.B.
Highlights: Direct growth of Mn(OH)2 /Co(OH)2 nanocomposite over flexible carbon cloth substrate for binder free supercapacitor electrodes In two electrode configuration electrode delivers a maximum specific capacitance of 385 F/g at 5 mV s −1 . At a specific power of 1 kW kg −1, the supercapacitor electrode exhibits a specific energy of 27 Wh kg −1 . The device retained 96% of its maximum specific capacitance even after 6000 charge-discharge cycles at 2 A/g. Abstract: The present work reports, direct growth of binary metal hydroxide ((Mn(OH)2 )/(Co(OH)2 )) nanocomposite on flexible carbon cloth substrate by a simple and affordable chemical bath deposition method. The as-prepared binder free binary metal hydroxide nanocomposite electrode exhibits a specific capacitance as high as 385 F g −1, in the symmetric two-electrode configuration in a stable potential window ranging from 0V to 1V. At a specific power of 1 kW kg −1, the supercapacitor gives a specific energy of 27 W h kg −1 . The device exhibits a cycling stability of 96% even after 6000 cycles of charge-discharge at a current density of 2 A g −1 . The structural and morphological analyses of the electrodes after the stability measurements, further confirm the superior electrochemical stability of the binary nanocomposite electrode. The results demonstrate the potential of Mn(OH)2 /Co(OH)2 nanocomposite for energy storage applications. Graphical Abstract: Image, graphical abstract